Hubungan Kualitas Sistem, Informasi, dan Pelayanan dengan Kepuasan Pengguna Surveilans Penyakit Tidak Menular di Palembang - Yuniarti, Ira Fitria; Novrikasari, Novrikasari; Misnaniarti, Misnaniarti (Window of Health : Jurnal Kesehatan, 2021)
Application of Non-Communicable Disease Surveillance System has been introduced since 2014, and for 5 years the application in the form of reporting of Non-Communicable Diseases through the web has not been running optimally in the City of Palembang. To analyze the causes, researchers used the theory of the success of DeLone and Mc Lean's information systems. This study aims to determine the relationship between system quality, information quality, and service quality with user satisfaction on the Use of Non-communicable Disease Surveillance System Applications in Palembang City. This research uses descriptive analytic design with cross-sectional approach. This study involved all the managers of the Non-Communicable Disease program in 41 Public Health Centre in the Palembang City Area totaling 65 people. By using an existing questionnaire, the research data were processed using chi square using the SPSS application. The results showed a relationship between system quality and user satisfaction (p-value = 0.001), a relationship between information quality and user satisfaction (p-value = 0,000), and a relationship between service quality and user satisfaction (p-value = 0,000 ). This study proves the relationship between system quality, information quality, and service quality with user satisfaction in the Application of Non-Communicable Disease Surveillance Systems in the City of Palembang